An audiological profile of keratitis-ichthyosis-deafness syndrome - Lonhare, Rahul Kumar; Ansari, Imran; Sahu, Preeti; Mahallik, Debadatta (International Journal of Research in Medical Sciences, 2022)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare genetic multi-system disorder. It is characterized by defects of the surface of the corneas (keratitis), red, rough thickened plaques of skin (erythrokeratoderma) with sensorineural hearing impairment. The skin of the palms of the hand, soles of the feet and the nails may be affected. Most cases are sporadic caused by mutations in the (GJB2 gene). Most cases are sporadic but familial cases with autosomal dominant inheritance have been reported a rare congenital ectodermal disorder characterized by vascularising keratitis hyperkeratotic skin lesions and hearing loss. The 2-year male child was presented at audiology and speech pathology unit department of ENT at Pt. Jawaharlal Nehru memorial hospital, Raipur, patient came with the complaint of inability to hear since birth. The present report outlined persistent severe sensorineural hearing loss in child with KID syndrome.